Zwischen Prager Frühling und Dissidententum - Korowin, Elena (My University, 2018)
What did the year 1968 mean for the Soviet Union? It was mainly the end of the Khrushchev Thawperiod that found its expression in the Prague Springand the dissident movement. There are tendencies to compare this fateful year in the Soviet Union with that in the West. Although there are similarities, but the more differences can be detected. For example, hardly someone would search for feminist tendencies or aesthetics in the work of Soviet artists of that time. This is the main task of this article: In the first step, the nonconformist scene of the 1960s will be searched for female protagonists and in the second step it will be examined, whether there were certain couplings in the work of female artists of the Soviet underground and nonconformist art scene with political and social protest forms, or whether it is rather characterized by the absence of such practices.
Was machten sowjetische Künstler_innen des Undergrounds?
Keywords: 700 Künste, Bildende und angewandte Kunst; Feminismus und Kunst; Sowjetische Kunst